PENGARUH BAHAN STEK BATANG DAN MEDIA TANAM TERHADAP PERTUMBUHAN VEGETATIF JERUK LEMON (Citrus limon L.) - M. Darul Anwar; Titik Irawati; Cahyo Septiyantoro (Jurnal Ilmiah Hijau Cendekia, 2019)
Lemon is a fruit whose prospects for agribusiness are high in Indonesia. One abstacle in lemo agribusiness is the lack of availability of seeds ready for planting from seeds so that an alternative is needed to overcome the shortage of seeds using stem cuttings. The purpose of this study is to influence the effect of cuttings and planting media that are suitable for vegetative propagation of lemon (Citrus limon) citrus plants. The research was conducted in february to may 2017 in the fields of sumberagung village, wates district, kediri regency. The research design used in this study was a randomized block design with two factors and each factor had three replications. The results showed that there was a real interaction on the combination of treatment the effect of stem cuttings and planting media on the vegetatitve growth of lemon to shoot length at 40 day after seedling, and there was a significant effect due to a single factor influence of stem cuttings and planting media vegetative growth of lemon to number of shoots at age (40, 50, and 60 days after seedling) and shoot length at age (50 and 60 days after seedling), but no real interaction occurred in combination and single factor in treatment of root length and number of roots